A Study of Photocatalytic Activity Towards the Degradation of Organic Pollutants Under Visible Light Irradiation: Exploring the Visible Light Photocatalytic Activity of a Novel Material for Organic Pollutant Degradation (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study investigates the photocatalytic activity of a specific material in the degradation oforganic pollutants under visible light irradiation. The growing concern over environmental pollutioncaused by organic pollutants necessitates the development of efficient and sustainable degradationmethods. Photocatalysis, which utilizes semiconducting materials to harness solar energy and degradepollutants, has emerged as a promising solution. However, most studies focus on photocatalytic activityunder ultraviolet (UV) light, limiting its practical application. In this research, we explore the visible lightphotocatalytic activity of a novel material and evaluate its performance in degrading organic pollutants.The material's synthesis, characterization, and photocatalytic experiments were conducted, and thedegradation efficiency of various organic pollutants was measured. The results demonstrate thematerial's significant visible light photocatalytic activity and its potential as an effective tool for organicpollutant degradation under solar light.